Impact of FOMO Syndrome on Adolescent Mental Health: A Systematic Review - Guzmán-Brand, Víctor Alfonso; Gélvez García, Laura Esperanza (Pensando Psicología, 2025)
Objective: To identify the characteristics and implications of Fomo syndrome on adolescent mental health.Methodology: A systematic literature review covering the last five years and using digital databases was performed. Studies were selected that met previously established eligibility criteria, including representative samples of adolescents.Results: Fomo syndrome, known as the fear of missing out, is characterized by a shift in attention toward activities posted on social media by others, which generates anxiety and concerns about social exclusion. According to the reviewed studies, this constant search for connection can have negative consequences for mental health, especially in adolescents.Discussion: Excessive use of smartphones and social media has been identified as a predictor of Fomo syndrome, and mental disorders may play a determining role in its development.Conclusions: It is crucial for adolescents to acquire digital and socio-emotional skills, such as digital intelligence, self-esteem, and emotional self-efficacy, to establish a healthy relationship with technology. These skills are essential for adolescents to use technology appropriately and mitigate potential negative effects on their mental health.
Keywords: Fomo syndrome; addiction; mental health; technology; adolescence